Elderly People's Joint Pain at Posyandu Pelangi Nusantara Surabaya - Martha, Anastasia Putu; Astuti, Martha Sri; Dilaga, Gagah Ahmad; Santosa, Marcelina Beatrice Elsandari; Renata, Levia (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: The context of this study is that older adults face a wide range of health issues, of which pain is a common and serious one that is frequently linked to functional impairment. People 65 years of age and older have joint discomfort twice as frequently as young adults. Finding out how much joint discomfort the elderly at Posyandu Pelangi Nusantara endured was the study's main goal. Purposes: The aim of this study is to determine the prevalence of joint pain based on anatomical location among the elderly at Posyandu Pelangi Nusantara. With an average age of 65, the 66 senior respondents in this descriptive study were found in Posyandu Pelangi Nusantara, Darmo District, Surabaya. Methods: It was conducted using the simple random sampling method. The NRS (Numerical Rating Scale) is the tool used in this study. The NRS, a widely used instrument for pain assessment, has demonstrated high inter-rater reliability (Cronbach’s alpha > 0.9) and validity in previous studies. Result: According to the study's findings, 64% of participants reported experiencing pain, 41% reported having knee discomfort, 38% lower back pain, 15% shoulder pain, and 6% neck pain. This is in line with other studies showing that the majority of elderly respondents experience joint pain at a moderate level. This may occur due to several chronic conditions experienced by the elderly, such as high uric acid levels or excessive physical activity, which can increase the intensity of joint pain. To enhance the quality of life for the elderly, more study may be done to determine the causes of pain and develop strategies to lessen these concerns. Conclusion: Most of the research participants, who were the elderly residents of Posyandu Pelangi Nusantara, complained of joint pain. Knee joint pain is the most common complaint. Suggestions for future research include recommending community-based health intervention programs and conducting further studies to explore the factors causing pain.